Photosensitivity From Avapritinib: Pharamacovigilance Analysis - Ajit Venkatakrishnan; Brandon Chu; Pushkar Aggarwal (JMIR Publications, 2022)
Certain protein kinase inhibitors have been reported to cause photosensitivity. Avapritinib is a tyrosine kinase inhibitor that was approved in January 2020. The aim of this analysis was to determine if a statistically significant signal exists between Avapritinib and photosensitivity in the real-world population. A disproportionality analysis was conducted using the Food and Drug Administration Adverse Event Reporting System (FAERS) from January 1, 2020, to December 31, 2021. A literature review was also performed to identify case reports of Avapritinib-induced photosensitivity. A total of 13 adverse event reports with Avapritinib as the drug and photosensitivity as the reaction were identified in FAERS. Avapritinib was the suspect drug in all 13 reports, and in 12 of the 13 reports, Avapritinib was the only drug listed. Disproportionality analysis found a proportional reporting ratio of 11.0, χ21=107, reporting odds ratio of 11.0, and a lower limit of the 95% CI of the information component of 2.1. The literature review found 1 case report of Avapritinib-induced photosensitivity in a patient who had been taking Avapritinib 300 mg daily for 5 months. A statistically significant signal was found between Avapritinib use and photosensitivity. Clinicians should continue to balance the benefits and risks when prescribing Avapritinib to patients.